Optimization Hotel Staff in Uncertain Condition Using Integer Linear Programming - Indri Hapsari (Conference Series, 2020)
Nature and man-made disasters have a significant impact on the tourism sector, either immediately or in the long term, disrupting the sustainability of tourism. Even decent planning has been carried out on the basis of previous experience, there is still a new challenge to be met as an impact of reducing sales. One of the problems is the number of hotel workers who have to stay in the tourism crisis. The goal is to provide a defined planning so that hotel managers and staff can prepare for the fluctuation of hotel occupancy. Modelling the demand of hotel guests and the availability of hotel staff is based on the method of aggregate production planning with the optimization result of integer linear programming. The effect is the number of hotel workers for each time , taking into account no disappointment on the part of hotel guests and reducing the cost of recruitment and lay-off of hotel staff. Case study is taken from the hotel occupancy in Bali before and during the Covid-19 pandemic, to demonstrate how the model works to quantify the number of workers required.